Endemic occurrence of Mycobacterium kansasii in water-supply systems - Kaustová, J; Olsovský, Z; Kubín, M; Zatloukal, O; Pelikán, M; Hradil, V (Journal of hygiene, epidemiology, microbiology, and immunology, 1981)
Of a total number of 1079 drinking water and colliery service water samples examined in an area of the North-Moravian Region Czechoslovakia, characterized by endemic occurrence of M. kansasii infections, 233 [21.6%] samples were found to be contaminated by mycobacteria, of these 20 [1.9%] by M. kansasii. Of additionally examined 510 water samples from the municipal water-supply network, which were collected in hospital laboratories and clinical departments as well as in the households of patients with M. kansasii infection and their possible contacts, 171 [33.5%] samples showed presence of mycobacteria, of these 18 [3.5%] were M. kansasii-positive. This mycobacterial species was isolated from the drinking water samples collected in two hospitals in the core of the endemic area, e.i. in the district of Karviná. In the district of Ostrava, where the drinking water supply, bot for colliery and households facilities, is provided from the same water-supply system, the presence of M. kansasii in the municipal water-supply network was not proved, but it was isolated from 5 samples of colliery drinking water. Further 114 samples taken from the local water treatment plant supplying the endemic area with drinking water were found to be free of M. kansasii species.
Keywords: Mycobacterium; Humans; Water Microbiology; lidé; Water Supply; mikrobiologie vody; Czechoslovakia; Mycobacterium Infections; mykobakteriózy; zásobování vodou; Československo